2012
DOI: 10.1210/jc.2011-2197
|View full text |Cite
|
Sign up to set email alerts
|

Higher Rates of Bone Loss in Postmenopausal HIV-Infected Women: A Longitudinal Study

Abstract: HIV+ postmenopausal minority women had lower BMD, increased bone turnover, and higher rates of bone loss than HIV- women. These features may place these women at increased risk for fracture as they age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 45 publications
5
69
2
Order By: Relevance
“…37 Studies conducted among HIV-infected women show varying results. 6 We found a significant, albeit modest, correlation between lower baseline BMD and subsequent gain in BMD at the total hip, with baseline total hip BMD accounting for only 3.6% of the variance in the total hip BMD change over time. We may be limited by the fact that our baseline DXA scans do not reflect a true baseline for the participants, as the median time since HIV diagnosis was 4.8 years and all had at least 2 years of suppressive cART exposure at time of first DXA scan.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…37 Studies conducted among HIV-infected women show varying results. 6 We found a significant, albeit modest, correlation between lower baseline BMD and subsequent gain in BMD at the total hip, with baseline total hip BMD accounting for only 3.6% of the variance in the total hip BMD change over time. We may be limited by the fact that our baseline DXA scans do not reflect a true baseline for the participants, as the median time since HIV diagnosis was 4.8 years and all had at least 2 years of suppressive cART exposure at time of first DXA scan.…”
Section: Discussionmentioning
confidence: 62%
“…[4][5][6] In comparison to controls from NHANES matched by age, sex, race, and BMI, our cohort had significantly lower T-scores at the femoral neck with almost twice as many persons with osteopenia and osteoporosis. These findings confirm other data regarding the robust association of HIV infection with low BMD.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The proximal femur is an important anatomical site for fracture, and femur fractures are usually accompanied with high morbidity and mortality (12). As HIV-infected individuals live longer through effective ART, HIV-related bone deterioration is superimposed upon age-related bone deterioration and is expected to result in greater rates of fragility fractures than in the general population in the near future (13,14). In addition to the effect of HIV infection, it has been shown that ART exacerbates bone loss (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…This chronic inflammation may contribute to the development and progression of bone loss, as indicated by the bone turnover markers N-telopeptide, C-telopeptide, and TNF->. 79,82 BMD, measured by dual-energy x-ray absorptiometry, has been found to decrease by 2% to 6% at both the hip and the spine, followed by stabilization within 1 to 2 years of ART initiation. 83,84 Specific antiretrovirals may be more likely to impact BMD than others.…”
Section: Bone Diseasementioning
confidence: 99%